LEARNING BASIC MOTION OF SOCCER WITH APPOACH PLAY - Haryono (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
The purpose of this study was to pruduce a basic learning model of motion to play soccer with the approach of the fifth grade elementary schoolstudents. In addition, this research was conducted to obtain more information about: the development and application of learning models to approach playing for elementary School fifth grade student, and the effectiveness, efficiency and appeal of the development of basic learning model of motion with the approach play soccer for School fifth grade student basic. The design of this study used a research design adopted from Brog and Gall. While the Subjects in this study were 38 fifth grade student of SDN 6 Pahandut, East Palangka Raya.The instrument used in this study is observation and interviews to collect data on: (1) needs analysis, (2) evaluation of the experts, (3) limited trial(trial within small groups), and (4) the main trial (trial field). Based on the results of a small group of test scores obtained by 272 of a maximum score of 312 or an average percentage of 87% for the use of the model so that the overall use of these models can be categorized on the development of valid and suitable for use in learning basic soccer with approach motion for student playing Elementary School fifth grade. To See the effectiveness of the model using the valuation basic psychomotor kicking motion, drible, control,and headed home. Of scores of student learning outcomes at the field test obtained 73% of the expected criteria. Based on these result in can be concluded that: (1) the basic learning model of motion with the approach play soccer for primary school student fifth grade, student can learn affectively and efficiently (2) with a Learning model that has been development suitable for use in the process of learning the basic motion soccer in elementary school.